Orbital mass secondary to infantile acute lymphoblastic leukaemia. (3rd May 2016) - Hossain, Ibtesham Tausif; Moosajee, Mariya; Abou-Rayyah, Yassir; Pavasovic, Vesna
Abstract : An 8-month-old Asian infant girl was referred with a 1-week history of left periorbital swelling on a background of a narrowed left palpebral aperture over the preceding 8 weeks. There was no history of chronic illness, fever or other systemic features. Examination revealed a tender and fluctuant medial canthal swelling with associated periorbital haematoma. There were no other ophthalmic findings and neurological examination was normal. A MRI scan of the brain and orbit demonstrated abnormal soft tissue with features of an aggressive tumour in the left orbital region with no globe invasion. Peripheral blood smear revealed blast cells, confirmed by bone marrow aspirate. A diagnosis of infant acute lymphoblastic leukaemia was made. The patient was started on risk-stratified chemotherapy according to the Interfant-06 Protocol . The periorbital swelling resolved by day eight following a course of prednisolone, the patient continues on chemotherapy and is currently in molecular remission.